2010
DOI: 10.1097/rhu.0b013e3181eeb94f
|View full text |Cite
|
Sign up to set email alerts
|

Rare Cause of Thoracic Myelopathy

Abstract: Myelopathy due to ossification of ligamentum flavum was first described in 1938 by Anzai (J Jpn Orthop Assosc. 1938;13:305-316). This is a rare condition that has been described mostly in the far east, most commonly in Japan (Miyasaka et al, Am J Neuroradiol. 1983;4:629-632). Cases reported from the western hemisphere are rare, particularly in the African-American population (Wiseman et al, J Spinal Disord Tech. 2002;15:542-545). We report an African-American patient who presented with progressive back and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…3,31,32 Ossification of the ligamentum flavum is very rare among black patients, with only a few reports in the literature. 8,[50][51][52][53][54] In 1998, Pascal-Mousselard et al reported an unusual OLF in the thoracic spine in a black patient presenting with progressive spastic paraparesis. 8 Because of its rarity in black patients, OLF is a diagnosis of exclusion in this population.…”
Section: Discussionmentioning
confidence: 99%
“…3,31,32 Ossification of the ligamentum flavum is very rare among black patients, with only a few reports in the literature. 8,[50][51][52][53][54] In 1998, Pascal-Mousselard et al reported an unusual OLF in the thoracic spine in a black patient presenting with progressive spastic paraparesis. 8 Because of its rarity in black patients, OLF is a diagnosis of exclusion in this population.…”
Section: Discussionmentioning
confidence: 99%
“…OLF was first diagnosed by Polgar in 1920 and was traditionally viewed as a disease affecting East Asians with a predominance among Japanese. [5] However, recent case series and reports have also been published from North and South America, Africa, Middle East, India and Europe. [6] The higher prevalence among Japanese is thought to be attributed to the traditional custom of kneeling and standing, which causes increased mechanical stress on the thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
“…Re zo nans ma gne tycz ny (MRI) i to mo gra fia kom pu te ro wa (TK) uwi dacz nia ją ty po we, prze ro śnięte, wpu kla ją ce się do wnę trza ka na łu krę go we go, skost nia łe wię za dła żół te. MRI i TK po zwa la ją nie tyl ko po sta wić pra wi dło we roz po zna nie cho ro by, ale rów nież są nie zbęd ne to od po wied nie go pla no wa nia le cze nia ope ra cyj ne go, po zwa la jąc na wy ko na nie proce du ry ma ło in wa zyj nej, ogra ni czo nej wy łącz nie do pa to lo gicz nie zmie nio ne go seg men tu krę go słu pa [33].…”
Section: Clinical Symptomsunclassified
“…MRI and CT tests reveal typical ossified ligamenta flava, which are hypertrophic and penetrate into the spinal canal. MRI and CT examinations not only make it possible to establish a diagnosis, but are also essential in order to plan appropriate surgical treatment, so that a less invasive procedure can be used, limited exclusively to the pathologically changed segment of the spine [33].…”
Section: Le Cze Niementioning
confidence: 99%